2022
DOI: 10.3390/ijms23137092
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Schizophrenia and Metabolic Syndrome: The Role of Oxytocinergic Dysfunction

Abstract: The high prevalence of metabolic syndrome in persons with schizophrenia has spurred investigational efforts to study the mechanism beneath its pathophysiology. Early psychosis dysfunction is present across multiple organ systems. On this account, schizophrenia may be a multisystem disorder in which one organ system is predominantly affected and where other organ systems are also concurrently involved. Growing evidence of the overlapping neurobiological profiles of metabolic risk factors and psychiatric symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 334 publications
0
20
0
Order By: Relevance
“…Aside from the aforementioned risk factors, the use of secondgeneration antipsychotics by patients with schizophrenia have been shown to lead to key features of metabolic syndrome, including weight gain, obesity, impaired glucose tolerance, and dyslipidaemia (Henderson et al, 2015;Goh et al, 2022;Richards-Belle et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from the aforementioned risk factors, the use of secondgeneration antipsychotics by patients with schizophrenia have been shown to lead to key features of metabolic syndrome, including weight gain, obesity, impaired glucose tolerance, and dyslipidaemia (Henderson et al, 2015;Goh et al, 2022;Richards-Belle et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia is a psychiatric disorder affecting approximately 1% of the world population ( Goh et al, 2022 ). Compared to the general population, individuals with schizophrenia have significant reductions in average life expectancy by 14.5 years; this premature mortality is primarily attributed to physical illness, including type 2 diabetes mellitus and cardiovascular disease ( Papanastasiou, 2013 ; Afzal et al, 2021 ; Goh et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis showed that several pharmacogenetic studies found that single nucleotide polymorphisms in adrenergic α2, dopaminergic D2, serotonergic 5HT2C and melanocortin-4 receptor genes were significantly associated with antipsychotic-related weight gain ( 13 ). Dysregulation of insulin, cortisol, glucagon, cholecystokinin, adiponectin, ghrelin, leptin, orexin, prolactin and oxytocin has also been reported during treatment with antipsychotic agents ( 14 , 15 ). The possible impairment of the mitochondrial dynamics in the pathogenesis of metabolic syndrome in patients undergoing antipsychotic treatment has been suggested, although data to support this hypothesis are still insufficient ( 16 ).…”
Section: Metabolic Dysfunctions In Patients Undergoing Antipsychotic ...mentioning
confidence: 99%
“…We also investigated whether ACE-I/D polymorphism might influence plasma lipid and glucose levels among schizophrenia patients receiving antipsychotic treatment [ 14 ]. Schizophrenia patients (specifically those taking antipsychotic medication) are more likely to exhibit weight gain, lipid disturbance, and glucose dysregulation, which makes them an interesting group in which to study the genetic basis of dyslipidemia and diabetes [ 15 , 16 ]. Furthermore, among individuals from the general population, ACE-I/D polymorphism has been extensively linked to dyslipidemia, diabetes, and metabolic syndrome [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%